Analisis Komprehensif Injeksi Biopolimer Xanthan Gum (XCD) pada Model Fisik Sandpack untuk Optimasi Enhanced Oil Recovery - Dennies Marcelino Assa; Baiq Maulinda Ulfah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Preparation of XCD solution using 2.50 g of XCD powder and 500 mL of distilled water mixed with a magnetic stirrer at a speed of 1000 rpm for XCD solution viscosity value is 18.15 cP and density of XCD solution is 1.875 g/mL. Injecting the XCD solution using a syringe pump in order to get a stable rate when pushing fluid from inside the sandpack, water flooding is done first to see the sealing power in the sandpack with a recovery factor obtained of 90%. With 250 mL of XCD solution injected, it can push out 31 mL of light oil trapped in the sandpack and get a recovery factor of 98% from the sandpack. Sweep efficiency of water and XCD flooding obtained is 0.89 where the mobility ratio value (M < 1) is very good sweep efficiency that works and if the mobility ratio (M > 1) sandpack conditions have been damaged such as water fingering in the sandpack.